Reverse Culture Shock Shaping Personal Traits and Views: A Case Study of Malang Returnees from Surabaya : KEJUTAN BUDAYA TERBALIK YANG MEMBENTUK PANDANGAN DAN KEPRIBADIAN: STUDI KASUS PERANTAU MALANG DARI SURABAYA - Arrasyid, Muhammad; Edi Dwi Riyanto; Nadya Afdholy (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Reverse culture shock is the next level of culture shock phenomenon that is commonly caused by asymmetric locations and frequently happens to sojourners returning to their homeland. Cities like Malang and Surabaya are examples of asymmetrical locations that are highly contrasted in terms of life pace as Malang is slow-paced while Surabaya is fast-paced. This circumstance potentially establishes such culture shock phenomena. This study, therefore, aims to examine the culture shock and reverse culture shock phenomena experienced by sojourners by focusing on its influence in shaping their personal traits and views. This study is categorized as qualitative research. The data collection technique is in the form of interviews with the sojourners who have met the criteria. This study applied Mizerow’s theory of transformative learning to analyze the data. The result of this study reveals that all participants had undergone both culture shock and reverse culture shock experiences. They also showed indications of which phenomena have influenced their personal traits and views in certain perspectives, specifically in shaping gratitude traits..